If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 13 = -27 Reorder the terms: 13 + x = -27 Solving 13 + x = -27 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + x = -27 + -13 Combine like terms: 13 + -13 = 0 0 + x = -27 + -13 x = -27 + -13 Combine like terms: -27 + -13 = -40 x = -40 Simplifying x = -40
| 4X-4-3=0 | | 1+x=2x+b | | X/29=5 | | 27h-3h=35 | | -22x=418 | | 2b(b-8)=30 | | 8m+0.85=760 | | 15+6(-3-11)= | | 2/3t=5/2 | | y=1+0.75y+1+0.3r+3.5+(-1.0-0.1) | | 1x+y+13=180 | | -4x+6=-4x+3 | | 1=y-siny | | 68-2x=12 | | 2(X+A)=12 | | 18x-34=2 | | 6x-18=2(3x-9) | | 6x/x*3x=y | | 1x+40+y=180 | | -2x+12=2x-16 | | .966=y-siny | | 6x/x*3x | | 3*X-4=6 | | X^2-16-20=0 | | -x-9=-16 | | 7(x+2)=7x-4 | | 13x+21=6x+0 | | I=1.3-0.3(1+r) | | 4(7-3z)=4 | | 8x-16=4x-40 | | .5(c-1)=4 | | 13x+9=6x+16 |